Addiction to social networks and emotional exhaustion in university students studying Psychology at a private university in the city of Juliaca, 2022 - Condori Sinty, Tania (2023)
Objective: determine the relationship between addiction to social networks and emotional exhaustion in university students of the Psychology major. Methodology: non-experimental cross-sectional design, quantitative approach of a correlational study. The population was made up of 300 students from III to VII cycle of psychology. The instruments to evaluate were the Social Network Addiction Questionnaire (ARS), a test constructed and validated by Escurra and Salas (2014) in Peru, and the Emotional Exhaustion Scale (ECE), said test was created by Ramos, Maga and Moran, 2005, in the present investigation the version adapted in Peru by Lavaggi (2017) was used. Results: there is a relationship between addiction to social networks and emotional exhaustion (Rho=0.555; p<0.05), which is a moderate and significant relationship that indicates that 55% of addiction behavior to social networks is related to emotional exhaustion. . This effect has an impact on the dimensions and relationships can be observed that range between Rho=0.496 to Rho=541 with significances less than 0.05. Conclusion: with higher levels of addiction to social networks, greater emotional exhaustion.